Inovasi Kemasan dan Perluasan Pemasaran Usaha Rempeyek di Yogyakarta - Siska Candra Ningsih; Kintoko; Puji Handayani Putri (Universitas Lancang Kuning, 2020)
The business group of Peyek 3E is a home industry business which is managed in a simple by a group of housewives in downtown of Yogyakarta. The business is run to improve the family’s economy. Peyek is produced and packaged simply with simple tools so that it is oily and packaged in a simple way. The Peyek 3E business group is assisted to improve the quality of its production and expand marketing. This activity goes through 4 steps, namely preparation, implementation, evaluation, and reporting. The results of service activities can be seen from the production aspect and marketing aspects. From the production aspect, the resulting project is no longer oily. Business already has a business license and PIRT sertificate. Product packaging is more attractive, designed according to the packaging standards of the Department of Health. From the marketing aspect, products have been sold at convenience stores and online. Additionally, the sales turnover increased.